Study of Seagrass Beds Condition Nearby Waters in Mokupa Village, Tombariri District, Minahasa Regency - Lasut, Nicole Theresa; Tilaar, Sandra O.; Sondak, Calvyn F. A.; Rampengan, Royke M.; Sinjal, Chatrien A. L.; Rembet, Unstain N. W. J. (Jurnal Ilmiah Platax, 2023)
The existence of seagrass beds in a shallow water environment has an important ecological role for the organisms that depend on this ecosystem. This research was conducted with the aim of knowing the types of seagrass and the condition of the seagrass beds in the waters near Mokupa Village, where the beach is between Mokupa Resort and Lotus Resort Manado. The method used is a quadrant transect (vertically to the shoreline), the coordinates point 1°24'53" N 124°42'22" E is transect 1, 1°24'54" N 124°42'22" E is transect 2,  and 1°24'56.7" N 124°42'23.5" E is transect 3. In this study, 5 species of seagrass were found, namely: Syringodium isoetifolium, Cymodocea rotundata, Thalassia hemprichii, Enhalus acoroides, and Halophila ovalis. Cymodocea rotundata had the highest average seagrass cover per species, 15.349%, and Enhalus acoroides had the lowest average seagrass cover, 0.053%. The condition of the seagrass beds at the study site was included in the unhealthy category with a seagrass cover of 31.432%. Keywords: Mokupa Waters, Seagrass conditions, Cover, Seagrass bed Abstrak Keberadaan padang lamun di lingkungan perairan dangkal memiliki peranan ekologis yang penting bagi organisme yang bergantung dalam ekosistem ini. Penelitian ini dilakukan dengan tujuan untuk mengetahui jenis-jenis lamun dan kondisi padang lamun di perairan sekitar Desa Mokupa, dimana pantai berada di antara Mokupa Resort dan Lotus Resort Manado. Penelitian ini mengikuti Pedoman Status Padang Lamun KEPMEN LH 200/2004. Metode yang digunakan yaitu transek kuadran (tegak lurus garis pantai), dengan titik koordinat Transek 1 1°24'53" N 124°42'22" E, Transek 2 1°24'54" N 124°42'22" E, Transek 3 1°24'56.7" N 124°42'23.5" E. Pada penelitian ini ditemukan 5 jenis lamun yaitu: Syringodium isoetifolium, Cymodocea rotundata, Thalassia hemprichii, Enhalus acoroides dan Halophila ovalis. Cymodocea rotundata memiliki rata-rata penutupan lamun per jenis tertinggi yaitu 15,349%, dan Enhalus acoroides memiliki rata-rata penutupan lamun terendah yaitu 0,053%. Kondisi padang lamun di lokasi penelitian termasuk dalam kategori kurang sehat dengan penutupan lamun sebesar 31,432%. Kata kunci: Perairan Mokupa, Kondisi lamun, Penutupan, Padang lamun